Historical population estimates : unraveling the consensus - Caldwell, John C.; Schindlmayr, T.
tbls.
pp. 183-204
Keywords: Poblacion Mundial; Africa; Americas; Asia; Oceania; Siglo XX; Proyecciones de Poblacion; Crecimiento Demografico